ANALISIS KELAYAKAN INVESTASI MARNING JAGUNG PADA INDUSTRI RUMAH TANGGA DESA KARANG ANYAR - Hananingrum Ayu Wulandari; Sutarni Sutarni; Analianasari Analianasari (Jurnal Penelitian Pertanian Terapan, 2021)
Corn is a source of food. Potential corn commodity to be developed as industrial raw material. The value of maize production in Lampung Province fluctuated in 2015-2019. The increase of economies of scale in Lampung Province can be overcome by processing corn into corn marning. The corn marning business in Karang Anyar Village is developed on a household scale. The purpose of this study was to analyze the investment and sensitivity level of maize in home industries in Karang Anyar Village, Gedong Tataan District, Pesawaran Regency. The data used in the study consisted of primary and secondary data. Primary data were obtained by interviewing, observing, and recording techniques, while secondary data were obtained from BPS, Koperindag Pesawaran, and other literature. This research is a survey research with qualitative and quantitative research types. The population that is the object of this research is 26 MSME actors with the type of household industry which is well known in Karang Anyar Village determined by the census method.  The analysis used is the analysis of investment criteria using Microsoft Excel and the calculation of linear trend analysis (Least Squares Method). Based on the results of calculations using investment criteria analysis, the NPV value is Rp.22,661,178.00, IRR is 61%, Net B/C is 2.29, BEP is achieved over 4 years 8 months 3 days, and PBP is achieved in a period 1 Year 4 Month 3 Days. The result of the sensitivity analysis to inflation is that 5% of the business is still feasible to run. Based on the results of the analysis carried out, it can be concluded that the IRT of corn marning is feasible to run and develop so that it is necessary to carry out business development.